2015
DOI: 10.1007/s11682-015-9444-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits

Abstract: Traumatic brain injury (TBI) remains one of the most prevalent forms of morbidity among Veterans and Service Members, particularly for those engaged in the conflicts in Iraq and Afghanistan. Neuroimaging has been considered a potentially useful diagnostic and prognostic tool across the spectrum of TBI generally, but may have particular importance in military populations where the diagnosis of mild TBI is particularly challenging, given the frequent lack of documentation on the nature of the injuries and mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 185 publications
(254 reference statements)
0
34
0
2
Order By: Relevance
“…We did not detect differences in the brain concentration of any MRS neurochemical between groups. Given that MRS‐detected neurochemicals are reported to be sensitive in vivo biomarkers of tissue pathology (Oz et al, ; Wilde et al, ), and our mitochondrial, apoptosis, and serum assays all suggest a beneficial effect of ubiquinol, we found the lack of neurochemical differences between groups to be surprising. However, mitochondrial and apoptosis assays were completed in cortical tissue, whereas the ROI for MRS mostly assessed subcortical tissue to avoid primary cortical damage (Figure ), which could contribute MR susceptibility artifacts from bleeding at the impact site.…”
Section: Discussionmentioning
confidence: 62%
“…We did not detect differences in the brain concentration of any MRS neurochemical between groups. Given that MRS‐detected neurochemicals are reported to be sensitive in vivo biomarkers of tissue pathology (Oz et al, ; Wilde et al, ), and our mitochondrial, apoptosis, and serum assays all suggest a beneficial effect of ubiquinol, we found the lack of neurochemical differences between groups to be surprising. However, mitochondrial and apoptosis assays were completed in cortical tissue, whereas the ROI for MRS mostly assessed subcortical tissue to avoid primary cortical damage (Figure ), which could contribute MR susceptibility artifacts from bleeding at the impact site.…”
Section: Discussionmentioning
confidence: 62%
“…Three, FreeSurfer can be used to generate unique, cohort‐specific control data that are transparent to the user. The issue of controls is becoming increasingly a topic of interest as unique hardware and demographic features likely affect the quality and the nature of the imaging data and consequently the volumetric output …”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging technology has made rapid advances over the past two decades revealing additional information about a number of neurologic processes. In particular, magnetic resonance imaging (MRI) has seen technological improvements in resolution, speed of acquisition, the addition of new sequences, and 3‐dimensional visualization of complex anatomy . Combined, these improvements have changed the way images are used in clinical settings and there are many efforts to establish more standardized evidence‐based uses that will inform clinical understanding of the extent, location, type, progression, and prognosis of an injury or disease process.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary clinical and research tools employed in examining the effects of TBI on brain structure has been medical imaging, especially quantitative or volumetric magnetic resonance imaging (MRI; [5, 6, 17, 61, 72]). Across the range of TBI severity, these studies have demonstrated a number of consistent findings including global atrophy (i.e., ventricle-to-brain ratio; [5, 65]), white and gray matter atrophy [6, 47, 64], regional vulnerability (temporal and frontal poles [4]) specific subcortical nuclei atrophy (i.e., thalamus, [43]), and cortical thinning [38, 66, 73]).…”
Section: Introductionmentioning
confidence: 99%